PEMBELAJARAN IPA MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DENGAN MEDIA ANIMASI DAN VIDEO INTERAKTIF DITINJAU DARI KEMAMPUAN VERBAL DAN GAYA BELAJAR SISWA - Sulistyawati, Rahayu Sri (LPPM IKIP PGRI Pontianak, 2010)
Based on the results of data analysis can be concluded: (1) there was an effect of learning Biology using model contextual learning through interactive media animation and video to ward student achievement, (2) there was an the effect of high and low verbal ability to ward student learning achievement, (3) there was an the effect of visual and kinesthetic learning styles to student learning achievement, (4) there was no interaction effect between contextual learning model using animations and interactive video with verbal ability on student achievement, (5) there is interaction effect between learning model using contextual learning with interactive animations and videos with students' learning styles to ward student achievement, (6) there is interaction effect between verbal ability and learning styles of students to ward student achievement, (7) there is interaction effect between learning model contextual learning using animation and video interactive media, verbal ability, and learning styles of students to ward student achievement.Â Keyword: contextual learning model, media animation, interactive video media, verbal ability, student learning styles, learning achievement, human circulatory system.